
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.



a) \(\frac{5}{12}=\frac{x}{72}\Rightarrow x=\frac{5.72}{12}=30\)
b)\(\frac{x+3}{15}=\frac{1}{3}\)
\(\Rightarrow x+3=\frac{15.1}{3}=5\)
\(\Rightarrow x=5-3=2\)
c)\(\frac{-2}{9}=\frac{x}{72}\Rightarrow x=\frac{-2.72}{9}=-16\)

\(72^{45}-72^{44}=72^{44}.\left(72-1\right)=72^{44}.71\)
\(72^{44}-72^{43}=72^{43}.\left(72-1\right)=72^{43}.71\)
Vì \(72^{44}>72^{43}\Rightarrow72^{45}-72^{44}>72^{44}-72^{43}\)

222222222222222222222222222222222222222222222

Lời giải:
$2^x+2^{x+3}=72$
$2^x(1+2^3)=72$
$2^x.9=72$
$2^x=72:9=8=2^3$
$\Rightarrow x=3$

1)15x-9x+2x=(15-9+2)x=8x=72
x=72:8=9
2)3x+2+3x=3x.32+3x=3x.9+3x.1=3x.(9+1)=3x.10=10
3x=10:10=1
3x=1=30
=>x=0
ko hiểu thì ? đừng k sai nha!


-2(2.x-8)+3(4-2.x)=-72-5(3.x-7)
<=>16-4x+12-6x =-72-15x+35
<=>16-4x+12-6x+72+15x-35=0
<=>65+5x=0
<=>x=-13
Nhớ tick cho mk hen😀

6 . 2x + 3 . 2x= 72
( 6 + 3 ) . 2x = 72
9 . 2x = 72
2x = 72 : 9
2x = 8
2x = 23
=> x = 3
6 . 2x + 3 . 2x= 72
2x . (6+3) = 72
2x . 9 = 72
2x = 8
2x = 23
x = 3
2\(^x\) + 2\(^x\)+3 = 72
2\(^x\) + 2\(^x\).23 = 72
2\(^x\).(1 + 23) = 72
2\(^x\).(1+ 8) = 72
2\(^x\).9 = 72
2\(^x\) = 72 : 9
2\(^x\) = 8
2\(^x\) = 23
\(x=3\)
Vậy \(x=3\)